2023
DOI: 10.1002/adom.202302500
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Tunable Polymer Stabilized Chiral Ferroelectric Nematic Liquid Crystal Microlenses

Kelum Perera,
Nilanthi Haputhantrige,
Md Sakhawat Hossain Himel
et al.

Abstract: Tunable optical lenses are in great demand in modern technologies ranging from augmented and virtual reality to sensing and detection. In this work, electrically tunable microlenses based on a polymer‐stabilized chiral ferroelectric nematic liquid crystal are described. The power of the lens can be quickly (within 5 ms) varied by ≈500 diopters by ramping an in‐plane electric field from 0 to 2.5 V µm−1. Importantly, within this relatively low‐amplitude field range, the lens is optically isotropic; thus, its foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The FNLC material used in this study is FNLC-919 (Merck), which was reported to exhibit the FNLC phase at RT (20 °C) 17) and has been utilized in fundamental and applied research fields. 29) The initial value of the birefringence of FNLC-919 was set as are determined for adjacent wavelengths by the procedure described above, where the ( ) l Dn can be well approximated by Cauchy dispersion and its coefficients were also determined at the same time. Searching for the multivariate that minimizes the difference between measured and simulated values with respect to ( ) l D and ( ) l Y , based on the polytope method as the best method for multivariate analysis, finally j t can be determined.…”
mentioning
confidence: 99%
“…The FNLC material used in this study is FNLC-919 (Merck), which was reported to exhibit the FNLC phase at RT (20 °C) 17) and has been utilized in fundamental and applied research fields. 29) The initial value of the birefringence of FNLC-919 was set as are determined for adjacent wavelengths by the procedure described above, where the ( ) l Dn can be well approximated by Cauchy dispersion and its coefficients were also determined at the same time. Searching for the multivariate that minimizes the difference between measured and simulated values with respect to ( ) l D and ( ) l Y , based on the polytope method as the best method for multivariate analysis, finally j t can be determined.…”
mentioning
confidence: 99%